Going Nuclear: How the Atom Will Save the World - Anam Murad Khan (CISS Insight Journal, 2025)
The book ‘Going Nuclear: How the Atom Will Save the World’ by Tim Gregory (PhD) is a seminal commentary on the enduring relevance of nuclear science. While the world struggles to find practical ways to achieve global net-zero, this book emerges as a timely contribution. Tim Gregory, a nuclear chemist within the British nuclear enterprise, a renowned author, and a regular presenter on British Broadcasting Corporation (BBC) Science, brings both expertise and passion to the nuclear discovery delights in the book. He employs scientific literacy and rational optimism to dispel decades-old fears of nuclear science. With his blend of human warmth and scientific proficiency, he deconstructs complex global security challenges and impediments to their nuclear solutions. The author articulates net-zero technologies, nuclear science, and nuclear energy through scientific reasoning. Gregory’s thirteen-chapter monograph offers a wide-ranging and well organized overview of nuclear science, tracing its intellectual trajectory from mythological origins to contemporary technological applications. In the opening chapters, he explains how the atom appears in both cultural imagination and empirical inquiry, moving from Promethean myths to the experimental validations of Röntgen, Becquerel, and Curie. This dual framing highlights the persistence of symbolic anxieties surrounding nuclear energy, even as its foundations rest upon reproducible observation and measurement. The main argument of the writer is that nuclear science, often portrayed as mysterious or uncontrollable, is in fact rational, comprehensible, and amenable to systematic management. By starting with the cultural and historical story of atomic discovery, he sets the interpretive lens through which subsequent technical and political discussions are to be understood.